2013
DOI: 10.1103/physreve.88.042316
|View full text |Cite
|
Sign up to set email alerts
|

Broadband ultrasonic spectrometry of polystyrene-cyclohexane critical mixtures

Abstract: Mutual diffusion coefficients, shear viscosities, and broadband ultrasonic attenuation spectra in the frequency range 100 kHz to 300 MHz have been measured for solutions of polystyrene in cyclohexane at two degrees of polymerization N and various temperatures near the critical. The exponent y(η) in the power law representation of the critical part in the viscosity deviates substantially from the universal value y(η) = 0.0435: y(η) = 0.028 (N = 288) and y(η) = 0.014 (N = 6242). Also, the adiabatic coupling cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Recently, however, it was found that the critical fluctuations of the polystyrene−cyclohexane binary system reveal clear indications for their coupling to the polymer conformational variations. 37 In a series of papers, 38−41 ultrasonic attenuation spectra of poly(ethylene glycol) oligomers, measured in the frequency range between 5 MHz and 2.5 GHz revealed two Debye-type relaxation terms with discrete relaxation times. These terms were discussed to be due to a three-state model of chain conformational transitions, namely equilibria between trans− trans and trans−gauche, trans−gauche and gauche−gauche, as well as gauche−gauche and trans−trans rotational isomers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, however, it was found that the critical fluctuations of the polystyrene−cyclohexane binary system reveal clear indications for their coupling to the polymer conformational variations. 37 In a series of papers, 38−41 ultrasonic attenuation spectra of poly(ethylene glycol) oligomers, measured in the frequency range between 5 MHz and 2.5 GHz revealed two Debye-type relaxation terms with discrete relaxation times. These terms were discussed to be due to a three-state model of chain conformational transitions, namely equilibria between trans− trans and trans−gauche, trans−gauche and gauche−gauche, as well as gauche−gauche and trans−trans rotational isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the spectra were too small-band to allow for reliable conclusions about the underlying modes of the local segmental motions . Other investigations were focused on the critical demixing behavior of polymer–polymer and polymer–low-weight solvent , mixtures. The contributions from noncritical processes in the ultrasonic spectra of such mixtures were largely masked by those from the critical fluctuations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation